The European Charter of Fundamental Rights and the Migratory Crisis: The Rights of Persons in need for International Protection put to the test - Gil,Ana Rita (2018)
The 2015-2016 migratory crisis created several changes to the rights recognised in the European Charter of Fundamental Rights for migrants, and also to the European Common Asylum Law and Policy. This paper analyses the several rights and principles that were challenged during this crisis. Firstly, rights to international protection and to non refoulement. Secondly, guarantees that are aimed at enforcing nuclear rights. Finally, rights that must be guaranteed to asylum-seekers while they wait for the final decision on their application. It concludes that an effective principle of solidarity amongst Member States is necessary to help to the most affected countries, and, thus, to provide an effective international protection to refugees.